THE UNIQUE COPY OF THE NINETEENTH CENTURY LITHUANIAN BOOKS: ABC-BOOK NAUJAS PIBELIS BY J. G. WEISS AT THE BRITISH LIBRARY IN LONDON - NAVICKIENĖ, AUŠRA (Knygotyra, 2015)
Lithuanian ABC-books being the most popular Lithuanian printings in the 19th century among other publications of mass demand as calendars, catechisms, prayer-books, books of songs, today became an unique part of Lithuanian printed heritage. That was especially characteristic for the Lithuanian ACBbooks of Lithuania Major and Lithuania Minor3 of the first part of the 19th century. An anonymous ABC-book Moksłas skaytima raszta lietuwiszka (1759–1867) published for Lithuania Major population was reissued 76 times. An ABC-book Naujas pibelis prepared by a priest and superintendent of Karaliaučius Johann Gottlieb Weiss (1762–1819) and addressed to Lithuanians living in Lithuania Minor was published 13 times4. No copy of the most of the editions survived till our days, and the ones that did survive are considered as unique or rare copies in the Lithuanian classification of rarities. A copy of Naujas pibelis (RB. 23. a. 4804) at the British Library in London is a unique example of Johann Gottlieb Weiss ABC-book edition that was not yet recorded in the publications of the Lithuanian national bibliography. The comparative analysis of the British Library copy and other three copies of the ABC-book editions that were issued before 18505 denies speculations that the British Library copy could be printed in 1795. According to the peculiarities of its contents and polygraphic design it resembles most the examples of editions of the third to fifth decades of the 19th century. Analysis of the book de visu also confirms the fact that it is a copy of unknown edition of the ABC-book prepared by Johann Gottlieb Weiss, but not a work of supposedly Johann Friedrich Zöllner as it is recorded in the catalogue of the British Library.